The virgin vote : how young Americans made democracy social, politics personal, and voting popular in the nineteenth century - Grinspan, Jon (The University of North Carolina Press, 2016)
There was a time when young people were the most passionate participants in American democracy. Drawing on hundreds of diaries and letters of diverse young Americans, this book explores how exuberant young people and scheming party bosses relied on each other from the 1840s to the turn of the twentieth century.